Acid dissolution of LiF/(NH4)3AlF6 mixtures obtained in the fluorination of α-spodumene with NH4HF2: Modeling and optimization - Resentera Beiza, Alexander Cristian Jesús (2023)
Lithium is an essential element in the current energy paradigm shift. Therefore, Li extraction from mineral sources has become a scientific and technological priority. Industrially, the mineral α-spodumene is heated to 1100 °C to obtain phase β and then digested with concentrated sulfuric acid at 250 °C. As an alternative, the extraction of Li from α-spodumene with molten NH4HF2 has been proposed as an efficient alternative method at low temperature (∼160 °C). However, the LiF obtained requires an acid leaching step to be solubilized and to separate the Li from other products. This research presents the modeling and optimization of the acid leaching operating parameters of the LiF/(NH4)3AlF6 mixture. This mixture was obtained by processing α-spodumene with NH4HF2 at low temperatures. The solids were characterized by XRD, SEM/EDS, and the Rietveld method. The leaching operating parameters investigated were solid/liquid ratio, sulfuric acid concentration, and leaching time. (NH4)3AlF6 dissolution and Li extraction were analyzed and modeled separately using artificial neural networks and least squares, respectively. The optimization stage of the process leads to (NH4)3AlF6 dissolution of 99% and Li extractions of 93%, working with 6% (v/v) sulfuric acid solution and an S/L ratio of 30 g/L for 24 min